Poor practices of medical and health sciences students for the prevention of hepatitis B viral infections in Ethiopia - Regassa, Belay Tafa; Fiseha, Genene (International Journal of Infection Control, 2019)
Abstract Hepatitis B virus is a serious global public health problem and health professionals, especially medical and health sciences students are at risk of acquiring infection through occupational exposure. Hence, this study was aimed at assessing medical and health sciences students’ knowledge, attitudes and practices towards HBV transmission and prevention.A cross-sectional study was conducted from February to March, 2017 among 190 medical and health sciences students. Study participants were selected using random sampling technique. Self-administered questionnaire was used to collect information. Data was analyzed using SPSS version 20.Out of 190 distributed questionnaires, all were returned with a response rate of 100%. Majority of the students, 107(56.3%), were in the age group 20 – 24 years. Almost all the respondents had good knowledge about hepatitis B Virus transmission, treatment and prevention. Majorities, 179 (94.2%), of students had good attitudes towards the importance of standard precautions, vaccine and post exposure prophylaxis for HBV prevention. However, the study participants had poor practices towards the prevention of Hepatitis B infections where 164 (86.3%) of the students had not vaccinated against and screened for the virus and 111 (58.4%) of them were not practicing of the standard precautions. This study indicates that participants had good knowledge and attitudes towards hepatitis B virus prevention. However, they had experienced poor practicing while giving healthcare services. Key Words: Poor practices, Prevention, Hepatitis B viral infection, medical and health sciences students